Quality of care for patients with diabetes done by family medicine team during the period 2013-2016 - Larisa Gavran; Salih Tandir; Suad Sivić; Fatima Topčić (Medicinski glasnik, 2018)
Aim: To assess whether the quality of diabetes care provided by a family medicine team changed over the course of four years and to identify potential gaps in our practice in order to improve it in the future. Methods: An audit was carried out for randomly selected 120 medical records (MC) from the Diabetes Registry of patients with type 1 or 2 diabetes mellitus treated by one family medicine team for four consecutive years, from 2013 to 2016. We examined demographic data (gender, age, diabetes type, family history), annual examinations (glycated haemoglobin, blood glucose, lipid profile, neurological examination, urinalysis, foot care, ocular fundus and body mass index), prescribed insulin or other drugs and patients' education. Results: Over the years females dominated with the maximum of 63% in 2013. In most years type 2 diabetes occurred in 93% of patients. The acceptable level of monitoring included examination of ocular fundus, lipid profile or total cholesterol, blood pressure, fasting and postprandial blood glucose with more than 80% annually. A low level of monitoring complications of diabetes was found on monofilament test, 26% in 2016, urinalysis, 20% in 2016 and examination of feet with the maximum of 46% in 2013. Outcome measurement showed satisfactory levels of glycated haemoglobin of 60% in 2014, blood pressure 76% in 2014, fast 56% and postprandial blood glucose of 73% in 2013. Conclusion: We still need to find effective interventions that will lead to improvement of care for patients with diabetes in family medicine.
Keywords: quality of care; diabetes; family medicine team